Optimalisasi Peran Komite Sekolah Terhadap Peningkatan Mutu Pendidikan di SMP Nasyrul Ulum Al-Aziziyah Samalanga Kabupaten Bireuen - Sarayulis (Khadem: Jurnal Pengabdian Kepada Masyarakat, 2023)
Quality of Education is a conscious effort and aims to improve the quality of education. Quality education is the creation of an educated society that can create something creatively and innovatively. In fact, the quality of education at SMP Nasyrul Ulum AlAziziyah Samalanga, Bireuen Regency, is still lacking in the quality of education. The formulation of the problem in this study is how to optimize the role of the committee towards improving the quality of Islamic education at SMP Nasyrul Ulum Al-Aziziyah Samalanga, Bireuen Regency, what are the obstacles to the optimal role of the school committee on the quality of education at SMP Nasyrul Ulum Al-Aziziyah Samalanga, Bireuen Regency, and what is the influence of optimization the role of the committee on the quality of education at SMP Nasyrul Ulum Al-Aziziyah Samalanga, Bireue Regency. The purpose of the research is to find out how the quality of education is at SMP Nasyrul Ulum Al-Aziziyah Samalanga, Bireuen Regency, to find out what are the constraints of the school committee in optimizing the quality of education at SMP Nasyrul Ulum Al-Aziziyah Samalanga, Bireuen Regency, and to find out how the effect of optimizing the role of the committee on quality education at Nasyrul Ulum AlAziziyah Middle School, Samalanga, Bireuen Regency. The research method used is a type of qualitative research with a descriptive phenomenological approach. The results of his research are the quality of education at SMP Nasyrul Ulum Al-Aziziyah Samalanga, Bireuen Regency, which means that the quality of education has reached 8 criteria for National Education Standards according to the BSNP. The optimal role of the School Committee for Quality of Education is that it has fulfilled the 7 roles in accordance with the RKTS to help improve the smooth running of teaching and learning activities in schools both in terms of facilities, infrastructure and technical education such as fostering students' attitudes and behavior, assisting efforts to stabilize schools, seeking sources of funding to help students who are unable to afford it, conduct school assessments, give awards for the success of school management, conduct discussions on the proposed School Income and Expenditure Draft Budget (RAPBS) and request schools to hold meetings for certain interests.